Developing English Pocket Book for Elementary School Students: Penelitian - Miftahul Fikri; Marham Jupri Hadi; Moh. Gufron (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
English language instruction in elementary schools faces challenges regarding language exposure, vocabulary mastery, and the availability of engaging, practical learning media. This study aimed to develop an English Pocketbook and assess its validity and practicality as a supplementary learning tool. The research employed the ADDIE R&D model, involving 27 sixth-grade students from SDN Kwangrundun, Central Lombok. Data were collected via expert validation questionnaires and feedback from students and teachers; these data were analyzed using percentage-based metrics and served as the basis for product revisions. Expert validation results reached 87.50% (highly valid), while student and teacher responses were 87.22% and 85%, respectively (both indicating high practicality). Consequently, the English Pocketbook was deemed valid and practical as a supplementary learning medium. However, as its effectiveness in enhancing vocabulary mastery has not yet been measured, further research incorporating pre-tests and post-tests is required.